Rhythm and booze: contesting leisure mobilities on the Transpennine Real Ale Trail - Thurnell-Read, Thomas; Robinson, David; Herbst, Jan-Peter; Spracklen, Prof Karl (Mobilities, 2021)
Ale Trails, where a series of pubs noted for serving real ale and craft beer are linked together along a prescribed route followed either on foot or by bus or train, are now a well-established activity in the UK and beyond. However, in some cases they have become associated with large groups of rowdy drinkers characterised by excessive consumption and disorderly behaviour. While copious research has focused on drinking urban leisure spaces, few studies have examined leisure mobilities involved in drinking in, and intoxicated mobilities through, rural and suburban spaces. This article uses Henri Lefebvre's concept of rhythmanalysis to analyse leisure mobility through the spaces constituting the Ale Trail - including pubs, train carriages, station platforms and village streets. In these spaces, the differing rhythms of diverse individuals and groups as they move through heterogeneous spaces on foot and by train give rise to both shifting alignments and conflicts. The article concludes with a discussion of the spatial, temporal and affective dimensions of alcohol consumption and demonstrates the relevance of rhythmanalysis concepts and methods for exploring contemporary forms of leisure mobilities.